In the ring with polycystic kidney disease--avoiding the knockout punch. - Adam, J; Pollard, P (2011)
Autosomal dominant polycystic kidney disease (PKD) is an inherited disease that results from mutations in either polycystin (PKD1) or polycystin 2 (PKD2), both of which are large, complex, and multifunctional proteins whose loss results in the development of numerous fluid-filled cysts and fibrosis that compromise renal function. A number of spontaneous and engineered mouse models of PKD have provided some understanding of many aspects of cyst development, modifier genes, and mechanistic pathways, but fall short of reproducing the human disease accurately. Two recent papers in The Journal of Pathology set out new models using miRNA, or inducible and targeted recombination, that achieve partial or timed suppression of Pkd1. Instead of knocking out Pkd1 immediately, or completely, these more subtle approaches may help deliver more faithful models of this significant human renal disease.